Leiomyosarcoma: a rare complication of uterine fibroid - Parveen, Shazia; Sabzposh, Noor Afshan; Kuraishy, Amina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine sarcomas are rare tumours of mesodermal origin. Malignant change occurring in uterine fibroid is termed as leiomyosarcoma. They constitute around 2-6 % uterine malignancies and 25-36% of uterine sarcomas. The tumour is common in women between the age group 40-50 years. It has an aggressive course & usually metastasis goes to the lungs. The prognosis for women with uterine sarcoma primarily depends on the extent of disease at the time of diagnosis and mitotic index. Women with tumor size >5 cm in maximum diameter have poor prognosis. These tumours should be diagnosed and managed with no delay and must be followed vigilantly as the rate of recurrence & metastasis is very high.